2014
DOI: 10.1186/s12905-014-0135-4
|View full text |Cite
|
Sign up to set email alerts
|

Sexual violence in the lives of first-year university women in Canada: no improvements in the 21st century

Abstract: BackgroundSummarizes the frequency, type, and context of sexual assault in a large sample of first-year university women at three Canadian universities.MethodsAs part of a randomized controlled trial assessing the efficacy of a sexual assault resistance education program, baseline data were collected from women between ages of 17 and 24 using computerized surveys. Participants’ experience with sexual victimization since the age of 14 years was assessed using the Sexual Experiences Survey--Short Form Victimizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 39 publications
2
45
0
1
Order By: Relevance
“…Third, the rate of prior victimization among women who were enrolled in the study was higher than the rates generally reported in studies involving a random sample of participants. 4 This was anticipated and was minimized by recruiting through psychology courses that offered rewards for participation. Reductions in risk were observed among women with prior victimization and among those without prior victimization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, the rate of prior victimization among women who were enrolled in the study was higher than the rates generally reported in studies involving a random sample of participants. 4 This was anticipated and was minimized by recruiting through psychology courses that offered rewards for participation. Reductions in risk were observed among women with prior victimization and among those without prior victimization.…”
Section: Discussionmentioning
confidence: 99%
“…The full study protocol and the baseline characteristics and sexual assault histories have been published previously 4,22 ; the study protocol is also available with the full text of this article at NEJM.org. The first author assumes responsibility for the fidelity of the report to the protocol and the accuracy and completeness of the data.…”
Section: Enrollment and Randomizationmentioning
confidence: 99%
See 1 more Smart Citation
“…This article aims to examine how students understand their university's sexual violence policy and the process of reporting sexual violence on campus. The work of DeKeseredy and Kelly (1993), DeKeseredy and Schwartz (1998), DeKeseredy, Schwartz, and Tait (1993), Dekeseredy, Schwartz, & Alvi (2000), Newton-Taylor, DeWit and Gliksman (1998), and Senn, et al (2014) are some of the only peer-reviewed research on campus sexual assault in the Canadian context. These authors did not investigate students' understandings of campus policies and responses regarding sexual violence.…”
Section: Policy Responses To Sexual Violence On Campusmentioning
confidence: 99%
“…In a study of 3187 university students, Brecklin (2004) noted that 57% of women reported being victims of childhood sexual abuse (<14 years old; Brecklin, 2004). These numbers transcend into adulthood, where some studies have found that between 53.5% to 58.7% of women have experienced some form of sexual victimization beyond the age of 14 (Brecklin, 2004;Senn et al, 2014). While the personality traits of victims of sexual violence map onto those identified above, that is, victims of sexual violence are less likely to be sexually assertive (Greene & Navarro, 1998;Livingston et al, 2007;VanZile-Tamsen et al, 2005) and may be socially avoidant (Classen et al, 2001), the personality traits of female victims of nonsexual violence has garnered limited empirical attention.…”
Section: Personality and Vulnerabilitymentioning
confidence: 99%